2021
DOI: 10.17645/si.v9i1.3729
|View full text |Cite
|
Sign up to set email alerts
|

Rational Actors, Passive and Helpless Victims, Neither, Both: EU Borders and the Drive to Migrate in the Horn of Africa

Abstract: This article argues that neither borders nor the ways in which migrants see them constitute significant deterrents to the migrants’ resolve to migrate. The argument is based on an investigation of migrants en route to Europe from the Horn of Africa and the ways in which they see EU external borders and how that contributes to the decision to migrate. The article advances critiques of rational choice models of migrant decision-making that are based mainly on economic factors and contributes to theoretical expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…One is that enhanced risk perception does not necessarily discourage people from trying to migrate irregularly. As research has shown, the target audience of migration‐information campaigns is well aware and informed about the risks of migration and life at places of destination (Bakewell & Sturridge, 2021; Nshimbi, 2021) Moreover, migrants and asylum seekers are far from being mere recipients of migration management discourses; they create and select different channels of information. The second limitation is that government measures to create jobs and provide education to prevent irregular migration are not sufficient to tackle the structural problems of unemployment and lack of opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…One is that enhanced risk perception does not necessarily discourage people from trying to migrate irregularly. As research has shown, the target audience of migration‐information campaigns is well aware and informed about the risks of migration and life at places of destination (Bakewell & Sturridge, 2021; Nshimbi, 2021) Moreover, migrants and asylum seekers are far from being mere recipients of migration management discourses; they create and select different channels of information. The second limitation is that government measures to create jobs and provide education to prevent irregular migration are not sufficient to tackle the structural problems of unemployment and lack of opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…These forms of enablement between migration and mobility categories clearly intersect with social inequalities: not every migrant can mobilise past experiences to the same effect (Bolay, 2021;Nshimbi, 2021), and being a citizen of some countries can limit one's possibilities to move legally (Mau, 2010). Using the lenses of the MMN, we can better understand the interplay between regulations and the subjective dimension of being on the move.…”
Section: Migration Through Mobility: Enablementmentioning
confidence: 99%
“…Research on (non-)participation in assisted return programmes (commonly termed Assisted Voluntary Return [AVR]) -which, in some contexts, is a key mode of return for irregularised migrants -has attributed varying weight to the role of conditions in the country of origin in return decisionmaking -likely due to differences in methodological approach -but seem to indicate that (perceived) conditions in the country of origin weigh strongly in decisions not to return . What emerges clearly from studies on the decision-making of (rejected) asylum-seekers in particular is that fear regarding -particularly security -conditions in the country of origin acts as a strong deterrent to return Müller-Funk, 2019;Nshimbi, 2021;. However, changing conditions in the country of origin can also dissipate or remove the original motivation(s) for asylum-seeking, thereby prompting a decision to return (Dubow & Kuschminder, 2021a).…”
Section: Structural Conditions Country Of Origin Conditionsmentioning
confidence: 99%
“…Second, when it is received, information may be dismissed or ignored by migrants if it is considered unhelpful or unreliable . Third, even where accurate information about the costs and risks of restrictive policies are accepted by migrants, these may be deemed of minor significance in relation to other factors, including conditions in countries of origin, such as persecution, conflict, poverty and acute social pressures, and the related opportunities perceived in potential destination countries, such as labour demand, political rights and freedoms (Crawley & Hagen-Zanker, 2019;Nshimbi, 2021).…”
Section: Migration-specific Policies That Shape Decision-making Regar...mentioning
confidence: 99%